2019
DOI: 10.1111/jgh.14908
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic resonance enterography for predicting the clinical course of Crohn's disease strictures

Abstract: Background and Aims Strictures are the most common Crohn's disease complication, but their natural history is unknown. This study aimed to characterize inflammation, predict prognosis, and understand the impact of drug therapy using magnetic resonance enterography (MRE). Methods Patients with a stricture diagnosed on MRE over a 5‐year period were reviewed for MRE disease extent and inflammation, clinical course, C‐reactive protein, response to anti‐TNF therapy, endoscopic dilatation, hospitalization, and surge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 21 publications
0
8
0
4
Order By: Relevance
“…Fernandes et al [45] confirmed these data, showing that a lower percentage of small bowel CD patients achieving transmural healing required surgery, hospital admission, and therapy escalation (0%, 3%, and 15.2%, respectively) compared to patients with endoscopic mucosal healing (11.5%, 17.3%, and 36.5%, respectively) or active disease (11.6%, 24%, and 54.3%, respectively) after 12 months of follow-up [45]. Interestingly, both the MRE characteristics (proximal bowel dilatation ≥30 mm diameter (OR: 2.98; 95% CI: 1.36-6.55), stricture bowel wall thickness ≥10 mm (OR: 2.42; 95% CI: 1.11-5.27), and stricture length >5 cm (OR: 2.56; 95% CI: 1.21-5.43)) [46], as well as the disease pathways diagnosed using MRE (presence of perianal disease (OR: 9, 95% CI: 2-39, p = 0.003), stenoses (OR: 3.4, 95% CI: 1-11, p = 0.04), or intra-abdominal fistulas (OR: 10.6, 95% CI: 2-46, p = 0.002)) [47], were significantly related with a higher risk of surgery. A study by Deepak et al [48] investigated the natural history of CD patients managed through a strategy of treating to a target of radiological transmural remission along with a median follow-up of almost 5 years.…”
Section: Predicting Outcomes With Magnetic Resonance Imagingmentioning
confidence: 99%
“…Fernandes et al [45] confirmed these data, showing that a lower percentage of small bowel CD patients achieving transmural healing required surgery, hospital admission, and therapy escalation (0%, 3%, and 15.2%, respectively) compared to patients with endoscopic mucosal healing (11.5%, 17.3%, and 36.5%, respectively) or active disease (11.6%, 24%, and 54.3%, respectively) after 12 months of follow-up [45]. Interestingly, both the MRE characteristics (proximal bowel dilatation ≥30 mm diameter (OR: 2.98; 95% CI: 1.36-6.55), stricture bowel wall thickness ≥10 mm (OR: 2.42; 95% CI: 1.11-5.27), and stricture length >5 cm (OR: 2.56; 95% CI: 1.21-5.43)) [46], as well as the disease pathways diagnosed using MRE (presence of perianal disease (OR: 9, 95% CI: 2-39, p = 0.003), stenoses (OR: 3.4, 95% CI: 1-11, p = 0.04), or intra-abdominal fistulas (OR: 10.6, 95% CI: 2-46, p = 0.002)) [47], were significantly related with a higher risk of surgery. A study by Deepak et al [48] investigated the natural history of CD patients managed through a strategy of treating to a target of radiological transmural remission along with a median follow-up of almost 5 years.…”
Section: Predicting Outcomes With Magnetic Resonance Imagingmentioning
confidence: 99%
“…Die aktuell gängige Definition beschreibt eine Einengung des Lumens mit einer prästenotischen Dilatation > 25 mm des vorgeschalteten Darmsegments [16,54,55]. Die Forderung nach einer prästenotischen Dilatation reduziert möglicherweise die Sensitivität für die Detektion von Stenosen [56,57,58,59,60]. Der Vorteil der Darmsonografie liegt darin, dass die Motilität des vorgeschalteten Darmsegmentes zur Identifizierung der Stenose als Kriterium mit herangezogen werden kann.…”
Section: Stenosierender Morbus Crohnunclassified
“…Inflammatory strictures can also be distinguished from fibrotic ones in CD by other combination modalities, such as the magnetization transfer (MT) ratio of magnetization transfer imaging with T2WI of conventional MRI 46 and dynamic contrast‐enhanced MRI with intravoxel in coherent motion 43 . In addition, MRE may predict disease progression and the need for future surgery in CD with strictures; surgery‐related MRE features include proximal bowel dilatation diameter ≥30 mm, stricture wall thickness ≥10 mm and stricture length >5 cm 47 …”
Section: Assessment Of Intestinal Stricturementioning
confidence: 99%